2021
DOI: 10.1016/j.ejrad.2021.109602
|View full text |Cite
|
Sign up to set email alerts
|

Texture feature-based machine learning classifier could assist in the diagnosis of COVID-19

Abstract: Differentiating COVID-19 from other acute infectious pneumonias rapidly is challenging at present. This study aims to improve the diagnosis of COVID-19 using computed tomography (CT). Method: COVID-19 was confirmed mainly by virus nucleic acid testing and epidemiological history according to WHO interim guidance, while other infectious pneumonias were diagnosed by antigen testing. The texture features were extracted from CT images by two radiologists with 5 years of work experience using modified wavelet trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…Interestingly, five of the seven features included in the top 5% predictive features of our study were texture related, thus indicating that the lesion hetereogeneity may help the differential diagnosis of GGOs. These results are in line with recent studies on the differential diagnosis of COVID-19 pneumonia 21 , 54 , 55 . For instance, Gulbay et al showed that the mean skewness and texture features were significantly different in GGOs when comparing COVID-19 and atypical pneumonia 21 .…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, five of the seven features included in the top 5% predictive features of our study were texture related, thus indicating that the lesion hetereogeneity may help the differential diagnosis of GGOs. These results are in line with recent studies on the differential diagnosis of COVID-19 pneumonia 21 , 54 , 55 . For instance, Gulbay et al showed that the mean skewness and texture features were significantly different in GGOs when comparing COVID-19 and atypical pneumonia 21 .…”
Section: Discussionsupporting
confidence: 92%
“…As demonstrated by Wu et al [ 26 ] CTTA could be used to rapidly differentiate COVID-19 from other infectious pneumonia. However, radiomic signature has been proven effective in classifying between stable and progressive group of COVID-19 patients with an AUC, sensitivity and specificity of 0.8, 81, and 74%, respectively [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics machine learning-based tool has been recently studied to evaluate the severity of COVID-19 [ 25 ]. A recent study proposed by Wu et al [ 26 ] have shown that despite the similar clinical and radiological manifestations in COVID-19 and non-COVID-19 patients, CT texture features may be a helpful toll to differentiate these two population. As a noninvasive and rapid imaging biomarker, texture analysis could improve COVID-19 chest CT diagnosis reducing false positive with the similar lung imaging pattern and allowing a better management of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of their ResNet50 deep model was compared by the performances of two radiologists, and their deep learning approach was shown to be better than human readers with 95.6% AUC. Different from the unsupervised DL approach for the problem, Wu et al [9] followed the supervised methodology. The texture features of CT scans were extracted by experienced radiologists.…”
Section: Covid-19 Diagnosis Via Chest Imagesmentioning
confidence: 99%